Weighted pseudo almost automorphic solutions to functional differential equations with infinite delay - Yong-Kui Chang; Shan Zheng (Electronic Journal of Differential Equations, 2016)
In this article, we first establish some results on composition of Stepanov-like weighted pseudo almost automorphic functions so called class r and class infinity under a uniform continuity condition with respect to L^p-norm. And then, we study the existence and uniqueness of weighted pseudo almost automorphic solutions to an abstract partial neutral functional differential equation with infinite delay with a Stepanov-like nonlinear term.